Kritik Sosial pada Novel "Book Shamer" Karya Asmira Fhea: Sosiologi Sastra - M, Asia; Ridwan, Ridwan; Nurlaila, Nurlaila (Nuances of Indonesian Language, 2024)
This research was conducted with the aim of looking for social criticism in the novel Book Shamer by Asmira Fhea, data was taken from the novel Book Shamer by Asmira Fhea. Data collection was carried out using library techniques, listening and taking notes. The data analysis methods used are descriptive analysis, content analysis, and comparative analysis by identifying elements in the novel, using Lucian Goldman's literary sociology theory. The results of this research show that there are five social criticisms in the novel Book Shamer, namely moral criticism about the ethics of communication on social media and the importance of empathy, educational criticism regarding the freedom to choose an educational path and a dismissive view of the field of literature, and family criticism which describes generational conflict related to appreciation. towards reading fiction. This research also emphasizes the importance of social awareness and appreciation of various types of knowledge and literary works. This study can show how literary works can be a medium for reflection and criticism of social reality. This confirms that literary works are not only entertainment, but also have an important role in forming social awareness.